Correlation Of Essential Micronutrient Metabolism In Adolescents With Neurocirculatory Dystonia Living In Conditions Of Iodine Deficiency - Sultanova Feruza Khoshimovna (Zien Journals, 2023)
Reproduction of offspring is a complex biological process in which not only the reproductive apparatus, but the entire organism as a whole is involved. Therefore, the causes leading to reproductive dysfunction must be sought not only in the reproductive system, but throughout the entire body.
Keywords: Metabolism; method; dysfunction